Pengaruh Model Pembelajaran Kooperatif Tipe Question Student Have (Qsh) Terhadap Hasil Belajar Kognitif Pada Materi Elektrokimia - SAPUTRA, ANSOR FIRMAN; SANTOSO, BIMO BUDI; LARASATI, CHRISTIANA NIKEN (Jurnal Ilmu Pendidikan Indonesia, 2019)
This study aims to determine the effect of the Cooperative Question Question Have (QSH) type of learning model on cognitive chemistry learning outcomes in Electrochemical material. The research methodology is a type of quasi experiment with a sample of class X students of SMK Negeri 2 Manokwari. The results showed that there was an effect of the QSH type learning model on cognitive chemistry learning outcomes in Electrochemical material at 22.4%.Â 